IMPLEMENTATION OF NOTARY RESPONSIBILITIES FOR THE ESTABLISHMENT OF A LIMITED COMPANY REPRESENTED TO THE SECOND PARTY (Study at City Notary Offices and Kediri Regency Notary Offices)” - Fanjanu, Nendya Yesi (International Significance of Notary, 2022)
Managing the establishment of a Limited Liability Company for some community groups is considered a hassle and a burden. Some people ask for help from other parties to arrange certificates of establishment, while others use it as a business opportunity by providing deed management representative services. This study aims to reveal the role of a notary in notarial duties, the status of the deed of establishment of a represented Limited Liability Company, and the execution of making authentic deeds through a second party. The research method used is juridical-empirical with primary, secondary, and tertiary data as well as qualitative analysis. The results of the study show that as long as the second party fulfills the requirements of a notary, obtaining the deed of establishment through them is not a problem. The signing of the deed by the business owner and the second party is an important moment in the process. The deed of establishment through a third party has legal status if it follows the procedure set by a notary. In conclusion, notaries in Kediri are familiar with the management of Limited Liability Companies through third parties with anticipatory steps to ensure compliance with applicable regulations. Keywords: Business Law; European Competition Law; Market; Predatory Pricing